Two new Pachyrhynchus (Curculionidae: Entiminae: Pachyrhynchini) from Misamis Occidental (Mindanao, The Philippines) - Bollino, Maurizio; Rukmane, Anita; Mohagan, Noel (Zootaxa, 2020)
Two new species belonging to the genus Pachyrhynchus Germar, 1824 (Curculionidae: Entiminae: Pachyrhynchini Schoenherr, 1826) from Northern Mindanao are described: Pachyrhynchus yoshitakei sp. nov. and Pachyrhynchus imitans sp. nov. The endophallus of Pachyrhynchus zamboanganus Yoshitake, 2012 is illustrated as well.